Reviewing the Implementation of the Global Minimum Tax on Tax Incentive Policies in Indonesia - Aisyah Tria Cantikasari; Dhanu Damai Buwana; Eka Ramadan Putra; Herandy Destian Anis Qorillahi; Luthfi Damarjati Riyanto; Sarham Agung Sukur Pelu (IPSAR (International Public Sector Accounting Review), 2026)
The implementation of the Global Minimum Tax (GMT) as part of BEPS 2.0 represents a significant change in the international taxation system. This study examines the implications of the Global Minimum Tax (GMT) on the effectiveness of tax holiday policies in Indonesia, particularly following the implementation of PMK 136/2024. Using a normative legal research method with statutory and conceptual approaches, this study evaluates the mechanisms of the Income Inclusion Rule (IIR) and the Qualified Domestic Minimum Top-up Tax (QDMTT), as well as their impact on the attractiveness of domestic fiscal incentives. The findings indicate that GMT has the potential to reduce the effectiveness of tax holidays when the Effective Tax Rate falls below 15%, thereby necessitating a redesign of incentive policies toward non-rate-based incentives. A comparative analysis with ASEAN countries reveals that regional policy responses are shifting from rate-based competition toward substance-based incentives. This study recommends the optimization of existing incentive instruments, namely investment allowance, research and development super deduction, and accelerated depreciation as alternatives that are more compatible with the GMT framework to maintain Indonesia's investment competitiveness.